Relationship between obesity-related parameters and chronic kidney disease in middle-aged and elderly populations in Taiwan: A community-based study - Chen, I-Ju; Hsu, Le-Tien; Lin, Ting-Wei; Chen, Jau-Yuan (Frontiers in Nutrition, 2022)
Globally, obesity is a major health problem and can markedly increase the risk of various diseases, including type 2 diabetes mellitus, hypertension (HTN), dyslipidemia, and chronic kidney disease (CKD). The association of obesity-related parameters, such as lipid parameters and their ratio, with CKD in clinical settings is not well understood. This study aimed to investigate the association of obesity-related parameters with CKD in the middle-aged and elderly population in Taiwan. This cross-sectional, community-based study recruited 400 participants (141 males and 259 females) aged 50 years or over from a community health promotion project at the Linkou Chang Gung Memorial Hospital (Guishan District, Taoyuan City) in 2014. Each participant completed a questionnaire including personal information and medical history during a face-to-face interview. Laboratory data were obtained from blood and urine sampling. The data were analyzed using t-test, chi-square test, Pearson’s correlation test, multivariate logistic regression, and receiver operating characteristic (ROC) analysis. A total of 81 participants were identified as having CKD (estimated glomerular filtration rate [eGFR] < 60 mL/min/1.73 m2 or urine albumin/creatinine ratio ≥ 30 mg/g), and their mean triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio was 3.37 ± 2.72. The mean TG/HDL-C ratio of the 319 participants without CKD was 2.35 ± 1.66. After adjusting for age, TG/HDL-C was significantly positively correlated with blood pressure, body mass index, waist circumference, and fasting plasma glucose but not low-density lipoprotein cholesterol. There was a negative correlation between TG/HDL-C and eGFR. Multiple logistic regression model analysis showed that TG/HDL-C was still significantly associated with CKD (OR: 1.17, 95% CI: 1.01-1.36, p = 0.04) after adjusting for multiple covariates. The cut-off point of TG/HDL-C as a predictor of CKD was 2.54 with an area under the ROC curve of 0.61 (95% CI: 0.53–0.68). There was a significant positive correlation between TG/HDL-C and several cardiovascular disease risk factors, including obesity indices. The TG/HDL-C ratio was significantly associated with the risk of CKD and demonstrated predictive ability for CKD in the middle-aged and elderly population. Further studies on its application in clinical settings are warranted.